Evaluation of nitrate leaching in a vulnerable zone: effect of irrigation water and organic manure application - Ruiz-Ramos, M.; Gabriel, J. L.; Vazquez, N.; Quemada, M. (Spanish Journal of Agricultural Research, 2011)
Sustainable agricultural practices are needed to minimize nitrate leaching. The crop-soil simulation model STICS coupled with a geographic information system was used to estimate the amount of NO3 – leaching and to assess the ability of alternative management practices to reduce NO3 – leaching in a nitrate vulnerable zone (NVZ) in La Rioja, Spain. Model performance was examined by comparing the simulations and measurements of irrigated grapevine crops (variety Tempranillo) over various soil types. The measurements were obtained from five pilot plots over a period of three years and included the mineral nitrogen, the water content of the soil profiles and the nitrogen content of the crops. The simulated and measured values were in satisfactory agreement with each other. Then, eight management scenarios were simulated, combining two NO3 – concentrations of irrigation water and four levels of organic manure applications. The simulations identified good agricultural practices (GAP) for mitigating NO3 – pollution. High soil mineral nitrogen (SMN) and water pollution were driven by both the NO3 – concentration of irrigation water and the level of organic manure application. The use of aquifer water for irrigation would lead to diminish aquifer pollution at the expense of maintaining high SMN, non desirable for grape quality production. River water would offer an opportunity for the recovery of soils and the improvement of underground water quality if the application of organic manure was limited according to soil type. Differences in NO3 - leaching of the NVZ soils depended more on their ability to store N than on their annual drainage.